PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII DI SMP NEGERI 4 MUARA BATANG GADIS - mahasiswa01 (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
This study aims: (1) To find out the improvement of students' mathematical problem solving by applying the Discovery Learning learning model to the subject of social arithmetic in class VII SMP Negeri 4 Muara Batang Gadis in the 2021/2022 academic year, (2) To determine the level of achievement of problem solving abilities. students' mathematics by applying the Discovery Learning learning model to the subject of social arithmetic in class VII SMP Negeri 4 Muara Batang Gadis for the 2021/2022 academic year, (3) To find out the management of learning carried out by the teacher by applying the Discovery Learning learning model based on problem solving on the subject of arithmetic Social studies in class VII SMP Negeri 4 Muara Batang Gadis teaching 2021/2022 This type of research is classroom action research. The level of problem solving ability in the first cycle is moderate with a class average score of 70.083 with 26 students (72.22%) Implementation of actions in cycle II, high The problem solving ability of students is high with a class average score of 80.47 with 35 students or 80.083% of all students. Thus it can be said that the class has been completed in learning, there are 80% of students who have a moderate level of problem solving ability.